Finite element analysis of the femoral diaphysis of fresh-frozen cadavers with computed tomography and mechanical testing - Yasushi Wako; Junichi Nakamura; Yusuke Matsuura; Takane Suzuki; Shigeo Hagiwara; Michiaki Miura; Yuya Kawarai; Masahiko Sugano; Kento Nawata; Kensuke Yoshino; Sumihisa Orita; Kazuhide Inage; et al. (Journal of Orthopaedic Surgery and Research, 2018)
Abstract Background The purpose of this study was to validate a diaphyseal femoral fracture model using a finite element analysis (FEA) with mechanical testing in fresh-frozen cadavers. Methods We used 18 intact femora (9 right and 9 left) from 9 fresh-frozen cadavers. Specimens were obtained from 5 males and 4 females with a mean age of 85.6 years. We compared a computed tomography (CT)-based FEA model to diaphyseal femoral fracture loads and stiffness obtained by three-point bending. Four material characteristic conversion equations (the Keyak, Carter, and Keller equations plus Keller’s equation for the vertebra) with different shell thicknesses (0.3, 0.4, and 0.5 mm) were compared with the mechanical testing. Results The average fracture load was 4582.8 N and the mean stiffness was 942.0 N/mm from actual mechanical testing. FEA prediction using Keller’s equation for the vertebra with a 0.4-mm shell thickness showed the best correlations with the fracture load (R 2 = 0.76) and stiffness (R 2 = 0.54). Shell thicknesses of 0.3 and 0.5 mm in Keller’s equation for the vertebra also showed a strong correlation with fracture load (R 2 = 0.66 for both) and stiffness (R 2 = 0.50 and 0.52, respectively). There were no significant correlations with the other equations. Conclusion We validated femoral diaphyseal fracture loads and stiffness using an FEA in a cadaveric study.